2007
DOI: 10.1177/0890334407307540
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Predictors of the Reasons Women Give for Choosing to Breastfeed

Abstract: The aims of this article are to outline the reasons Australian women give for initiating breastfeeding, identify unique predictors for these reasons, and use principal components factor analysis to determine factors that influence a woman's decision to breastfeed. Data were collected as part of a large longitudinal study investigating the breastfeeding behaviors and supports of women in Southern Queensland, Australia. The most common reason women (N = 562) gave for deciding to breastfeed was breast milk is bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…breastfeeding initiation, indicating that women who decide to breastfeed during early pregnancy are likely to initiate lactation after birth. Brodribb, Fallon, Hegney, and O'Brien (2007) reported that the women in their study decided whether or not to breastfeed before or in early pregnancy, and their decisions were based on baby-or mother-centered factors. The baby-centered factor most frequently reported was concern for infant health.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…breastfeeding initiation, indicating that women who decide to breastfeed during early pregnancy are likely to initiate lactation after birth. Brodribb, Fallon, Hegney, and O'Brien (2007) reported that the women in their study decided whether or not to breastfeed before or in early pregnancy, and their decisions were based on baby-or mother-centered factors. The baby-centered factor most frequently reported was concern for infant health.…”
mentioning
confidence: 99%
“…The baby-centered factor most frequently reported was concern for infant health. Mother-centered factors included either a preference to bottle-feed for convenience or a dislike of breastfeeding because of the reasons that included inconvenience, social barriers, or work-related barriers (Brodribb et al, 2007). Sociocultural, environmental, and personal factors are influential in a woman's decision to breastfeed.…”
mentioning
confidence: 99%
“…First, the women perceived that breast feeding is something 'natural', but did not indicate that latching was an 'easy' practice, as conversely reported by Hauck and Reinbold (1996). Moreover, the mothers perceived breast milk as ideal nourishment for their babies (Brodribb et al, 2007;Bai et al, 2009). In particular, colostrum was identified as very nutritive.…”
Section: Discussionmentioning
confidence: 72%
“…Mothers must be motivated to breastfeed to overcome physical and emotional distress that may occur when nourishing their babies (Kelleher, 2006;Forster et al, 2008;Hegney et al, 2008;Meedya et al, 2010). The thought that their personal milk is superior has been suggested to promote a high level of motivation to breastfeed (Brodribb et al, 2007), while qualitative studies have documented that breast feeding can differ from the expectations of the mother (Shakespeare et al, 2004). Breast feeding can be painful and physically exhausting and cause emotional distress (Kelleher, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…The routine care given by physicians working in primary care, home visits by nurses and midwives are indicated to increase breastfeeding initiation rates (Brodribb et al, 2007;Karp et al,2013). When pregnant women are examined about from whom they get information about breast milk and breastfeeding, 79.3% of them from midwives, 20.7% of them were found to get information from nurses.…”
Section: Discussionmentioning
confidence: 99%